The Buddhist Integration to Enhance the Life Quality of the Correctional Officers of Lamphun Provincial Prison - Dokklang, Somchat (MCU Haripunchai Review, 2025)
This research article has three main objectives: 1. to study the level of quality of work life of correctional personnel at Lamphun Provincial Prison, 2. to examine the relationship between Buddhist principles and the quality of work life of correctional personnel at Lamphun Provincial Prison, and 3. to propose guidelines for integrating Buddhism to enhance the quality of work life of correctional personnel at Lamphun Provincial Prison. The research design is a mixed-methods approach. The quantitative research population consists of 105 correctional personnel at Lamphun Provincial Prison. The quantitative research instrument is a questionnaire, which has a high reliability value. The statistics used for data analysis include frequency, percentage, mean, standard deviation, and Pearson correlation coefficient. For qualitative research, in-depth interviews were conducted with 10 key informants. The instrument used was an in-depth interview guide, and the data were analyzed using content analysis. The research results found that: 1) The overall level of implementation of the policy to promote the quality of work life for correctional personnel at Lamphun Provincial Prison is high (μ = 4.51, σ = 0.375), with all aspects also rated highly. These aspects include support, adequate and fair compensation, a safe and health-promoting work environment, job advancement and security, opportunities for development and utilization of individual capabilities, collaboration and relationships with others, personal rights in the workplace, work-life balance, and social contribution. 2) The relationship between Bhavanã 4 of the policy and the overall implementation of the policy to promote work-life quality for correctional personnel at Lamphun Provincial Prison is highly positive (r = 0.827**) and statistically significant at the 0.01 level. 3)The guidelines for applying Buddhist integration to promote the quality of work life of prison personnel at Lamphun Provincial Prison found that in the physical aspect, they practice morality; in the social aspect, they have honest occupations, maintain government discipline; in the mental aspect, they have love and compassion for their coworkers, and work with determination, following the agency’s logic and reasoning (intellectually, they found that they can analyze work and distinguish between what is good and what is not, and can conduct their daily lives without carelessness).